PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - YELDAWATI YELDAWATI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2022)
Classroom action research that aims to improve student learning activities in Class X TPM 2 at SMK N 2 Payakumbuh by implementing cooperative learning type STAD (Student Teams Achievement Division). As the subject of this research is Class X TPM 2 SMK Negeri 2 Payakumbuh, totaling 36 people in the even semester of the 2020/2021 academic year. This classroom action research was conducted in 2 cycles, each cycle consisting of 2 meetings. Collecting student activity data using the observation format that has been provided. The data collected during the action were analyzed using the technique of calculating the percentage. Learning outcomes data were analyzed using intervals. The results showed an increase in students' learning activities which was seen by increasing positive activities, and decreasing negative activities from cycle I to cycle II, where initially students who wanted to ask questions in cycle I only 4 people (11.11%) eventually increased in the second cycle became 19 people (52.78%) with an increase of 41.67%, the ability to respond or answer questions in the first cycle was only 5 people (13.89%) increased in the second cycle to 19 people (52.78%) experienced an increase (38.89%) and students who want to express opinions in the first cycle there are 3 people (8.33%) increasing in the second cycle to 20 people (55.55%) increasing 47.22% and increasing student learning outcomes on the test end of cycle I and cycle II. The average end of the cycle test, in the first cycle the average value was 66.8 and in the second cycle the average increased to 73.6. This shows that the use of the STAD (Student Teams Achievement Division) type of cooperative learning model can improve students' activities and learning outcomes. ABSTRAKPenelitian tindakan kelas yang bertujuan untuk meningkatkan aktivitas belajar peserta didik di Kelas X TPM 2 Di SMK N 2 Payakumbuh dengan menerapkan pembelajaran kooperatif tipe STAD (Student Teams Achievement Division). Sebagai subjek penelitian ini adalah Kelas X TPM 2 SMK Negeri 2 Payakumbuh yang berjumlah 36 orang pada semester genap Tahun Pelajaran 2020/2021. Penelitian tindakan kelas ini dilakukan dalam 2 siklus, tiap siklusnya terdiri dari 2 kali pertemuan. Pengambilan data aktivitas peserta didik dengan menggunakan format observasi yang telah disediakan. Data yang terkumpul selama tindakan dianalisa dengan menggunakan teknik melalui perhitungan persentase. Data hasil belajar dianalisa dengan menggunakan interval. Hasil penelitian menunjukkan adanya peningkatan aktivitas belajar peserta didik yang terlihat dengan meningkatnya aktivitas positif, dan menurunnya aktivitas negatif dari siklus I ke siklus II, Dimana yang awalnya peserta didik yang mau bertanya pada siklus I hanya 4 orang (11,11%) akhirnya meningkat pada siklus II menjadi 19 orang (52,78%) dengan kenaikan 41,67% , kemampuan merespon atau menjawab pertanyaan pada siklus I hanya 5 orang (13,89%) meningkat pada siklus II menjadi 19 orang ( 52,78%) mengalami kenaikan (38,89%) dan peserta didik yang mau mengeluarkan pendapat siklus I ada 3 orang (8,33%) meningkat pada siklus II menjadi 20 orang (55,55%) meningkat 47,22% serta meningkatnya hasil belajar peserta didik pada tes akhir siklus I dan siklus II. Rata-rata tes akhir siklus, pada siklus I nilai rata-ratanya adalah 66,8 dan pada siklus II rata-ratanya meningkat menjadi 73,6. Ini menunjukkan bahwa penggunaan model pembelajaran kooperatif tipe STAD (Student Teams Achievement Division) dapat meningkatkan aktivitas dan hasil belajar peserta didik.